Empreendedorismo de impacto social: o design thinking e a valorização do conhecimento tradicional - TAPAJÓS, Bárbara Fonseca Pinheiro Leão (Universidade Federal do Oeste do Pará, 2023)
The dialogical relationship between design and traditional communities, based on collaboration, aims to preserve and value traditions, a relationship that strengthens local innovative processes, strengthening social and environmental quality concepts. The research comes from the perspective of the problem experienced by a group of women in a traditional Community located in the Tapajos National Forest, which has as is subsistence the sale of vegetable oils from Amazonian species, which are extracted by hand, however, are sold as commodities, with low added value. In this sense, the work aimed to foster female empowerment and a culture of entrepreneurship among women who carry out craft work in traditional communities in the Amazon. For that, a methodological process of Design Thinking innovation was applied, which is based on the tripod: empathy, collaboration and experimentation, where the human being (the customer) is considered the center of the process. The results obtained were the visual identity, creation of the method that will serve as a basis for carrying out the training workshops, to obtain new bioproducts based on raw material from the Amazon, a market strategy plan, the empowerment of women representatives of the Community and the added value to activities carried out through traditional knowledge. Based on the results obtained, it is concluded that the application of the Design Thinking tool from the perspective of the concepts of innovation and entrepreneurship, added value to biobusiness, raising in these women the recognition of the importance of activities they carry out in the Community from the value they carry by traditional knowledge.